2018
DOI: 10.1055/s-0038-1672146
|View full text |Cite
|
Sign up to set email alerts
|

Does Voiding Cystourethrogram Exclude Posterior Urethral Valves in Late Presenting Cases?

Abstract: Introduction Delayed presentation of posterior urethral valves (PUVs) is a rare condition. Presentation and diagnosis of the patients with late PUVs are challenging. Voiding cystourethrogram (VCUG) is mainly practiced. In this study, we aimed to evaluate the children with late-presented PUVs, and the reliability of VCUG in this group. Materials and Methods Between January 2003 and December 2017 records of patients who were diagnosed with late-presented PUVs were analyzed. Delayed presentation of PU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Previous studies suggested that boys treated for PUV had improved urinary symptoms of DUI and NE. [3][4][5][6][7][8][9][10][11] However, in the present study, only two boys (17%) achieved daytime continence at 6 months after TUI and no boy was cured of NE at 6 months after TUI. Nakamura divided boys with PUV into two groups before TUI: those with a synergic pattern on urodynamics with a quiet electromyogram during filling and those with a dyssynergic pattern with increased electromyogram activity as the bladder filled.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous studies suggested that boys treated for PUV had improved urinary symptoms of DUI and NE. [3][4][5][6][7][8][9][10][11] However, in the present study, only two boys (17%) achieved daytime continence at 6 months after TUI and no boy was cured of NE at 6 months after TUI. Nakamura divided boys with PUV into two groups before TUI: those with a synergic pattern on urodynamics with a quiet electromyogram during filling and those with a dyssynergic pattern with increased electromyogram activity as the bladder filled.…”
Section: Discussioncontrasting
confidence: 78%
“…6 Infants and older children with delayed presentations of urethral valves may present with recurrent urinary tract infections, poor urinary stream, urinary frequency, nocturnal enuresis, urinary incontinence, anemia, and voiding pain or dysfunction. 2,[4][5][6][7]9,11,15,17 In Odetunde and colleagues' study of 21 patients with late presentation of PUVs, the median age was 3 years (2 days-13 years), and the mean duration of symptoms before presentation was 2.6 years. 18 Nineteen (91%) patients presented with urosepsis, while 8 (36%) patients presented with significant renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…While a few reports identify delayed presentation as a risk factor for poor renal function, others suggest that late presenting valves have good prognosis in terms of better recovery of lower urinary tract symptoms in the absence of hydroureteronephrosis. Eventually, there is a controversy about the prognosis of children with late presenting PUVs [11, 12]. The initial symptoms of delayed presentation of obstruction are age-dependent and nonspecific, and differ from those of early diagnosed PUVs [12].…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, there is a controversy about the prognosis of children with late presenting PUVs [11, 12]. The initial symptoms of delayed presentation of obstruction are age-dependent and nonspecific, and differ from those of early diagnosed PUVs [12]. In this case, because of the absence of PUV based on the previous cystoscopy finding in a different clinic, the case was diagnosed as non-neurogenic neurogenic bladder and followed up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation